Differential gonadotropin releasing hormone (GnRH) expression, autoregulation and effects in two models of rat luteinized ovarian cells - Sorianello, Eleonora Mariana (2005)
GnRH has been suggested to participate in corpus luteum function. Here we studied the expression of GnRH mRNA and peptide in two models of rat luteinized tissues: ovarian cells from PMSG–hCG treated prepubertal rats (SPO) and from intrasplenic ovarian tumors (Luteoma). A GnRH autoregulatory effect was evaluated as well as its action on cell proliferation and apoptosis. GnRH mRNA was present in SPO, isolated corpora lutea from SPO and Luteoma from 1 week to 7 months of development. In vitro cultures of Luteoma cells expressed 2-fold higher GnRH mRNA and 10-fold higher GnRH peptide than SPO cells. Buserelin (GnRH analog) increased GnRH mRNA and peptide expression in SPO but not in Luteoma cells. While basal proliferation was very low in Luteoma cells, SPO cells showed a significant increase in cell number by both the thymidine and the MTS methods after 72 h in culture. Buserelin induced a decrease in cell number in both cell types to a similar degree. Although basal apoptosis levels were higher in SPO than in Luteoma cells, Buserelin-induced apoptosis was only detected in Luteoma cells after 48 h treatment. These results show that the two types of rat, luteinized tissues, Luteoma and SPO, markedly differed in some intrinsic properties and in their local GnRH systems. Luteoma cells proliferate very weakly, express and secrete high amounts of GnRH, do not show an autoregulatory effect and respond to the decapeptide with apoptosis stimulation. In contrast SPO cells proliferate significantly, secrete low levels of GnRH but possess a positive, autoregulatory mechanism and respond to GnRH stimulation with impairment of proliferation.